NF-κB Pathway in Autoinflammatory Diseases: Dysregulation of Protein Modifications by Ubiquitin Defines a New Category of Autoinflammatory Diseases - Aksentijevich, Ivona; Zhou, Qing (Frontiers in Immunology, 2017)
Autoinflammatory diseases are caused by defects in genes that regulate the innate immunity. Recently, the scope of autoinflammation has been broadened to include diseases that result from dysregulations in protein modifications by the highly conserved ubiquitin peptides. Thus far these diseases consist of LUBAC and OTULIN deficiencies, and Haploinsufficiency of A20 (HA20). The Linear Ubiquitin Chain Assembly Complex (LUBAC) is critical for linear ubiquitiation of key signaling molecules in immune response pathways, while deubiquitinase enzymes, TNFAIP3/A20 and OTULIN, reverse the effects of ubiquitination by hydrolyzing Lys63 (K63) and linear (Met1) ubiquitin moieties, respectively, from conjugated proteins. Consequently, A20 or OTULIN-deficient cells have an excess of K63 or Met1 Ub chains on NEMO, RIPK1, and other target substrates, which leads to constitutive activation of the NF-kB pathway. Mutant cells produce elevated levels of many proinflammatory cytokines and respond to therapy with cytokine inhibitors. Patients with an impairment in LUBAC stability have compromised NF-kB responses in fibroblasts, while their monocytes are hyper-responsive to IL-1β. Discoveries of germline mutations in enzymes that regulate protein modifications by ubiquitin define a new category of autoinflammatory diseases caused by upregulations in the NF-kB signaling. The primary aim of this review is to summarize the latest developments in our understanding of the etiology of autoinflammation.